Economic evaluations of tobacco control mass media campaigns: a systematic review - Atusingwize, Edwinah; Lewis, Sarah; Langley, Tessa (BMJ Publishing Group, 2015)
BACKGROUND: International evidence shows that mass media campaigns are effective tobacco control interventions. However, they require substantial investment; a key question is whether their costs are justified by their benefits. The aim of this study was to systematically and comprehensively review economic evaluations of tobacco control mass media campaigns.